Ocean Terrain Analysis - Lepley, L. K. (The International Hydrographic Review, 2015)
A method to compute terrain parameters at regular intervals along depth profiles is described. This system of numerical analysis uses series of discrete data to extract quantitative geometrical properties; the system is easily programmed for digital computers.